SIMPLE, FAST, AND LOW-COST PRINCIPLES IN ELECTRONIC HEARINGS CIVIL CASES IN THE PENGADILAN NEGERI KELAS 1A PADANG: ASAS SEDERHANA, CEPAT, DAN BIAYA RINGAN PADA SIDANG ELEKTRONIK PERKARA PERDATA DI PENGADILAN NEGERI KELAS 1A PADANG - Velia, Vella Aqilla (ADHAPER: Jurnal Hukum Acara Perdata, 2025)
The judicial system in Indonesia applies the principles of simplicity, speed, and low cost as stipulated in Law No. 48 of 2009 on Judicial Authority. To realize simple, fast, and low-cost justice, reforms are needed to overcome obstacles and barriers in the administration of justice. Therefore, in 2019, the Supreme Court issued Supreme Court Regulation Number 1 of 2019 concerning Electronic Case Administration and Court Proceedings. The problems addressed in this study are how the principles of simplicity, speed, and low cost are applied in electronic hearings in civil cases at the Padang Class 1A District Court, the obstacles encountered in applying the principles of simplicity, speed, and low cost in electronic hearings in civil cases at the Padang Class 1A District Court, and how to solve them. This research is a type of empirical juridical research, namely research whose primary data is obtained through direct field research through interviews with respondents, namely judges, court clerks, and advocates. Then, a review of legal materials was conducted to obtain secondary data. Based on the results of the research, it can be concluded that the application of the principles of simplicity, speed, and low cost in electronic hearings (PERMA No. 1 of 2019) for civil cases at the Padang Class 1A District Court has been implemented well in accordance with the regulations issued by the Supreme Court (MA). The case registration and trial processes are conducted through e-Court, eliminating the need to visit the court. This saves money and time, as well as energy. The obstacles encountered are a lack of understanding of how to use e-Court, technological illiteracy, and unstable internet connections.